2015
DOI: 10.1016/j.sbspro.2015.01.1017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Self-esteem and Gratitude Disposition on Happiness in Pre-service Early Childhood Teachers

Abstract: AbstractfThe purpose of this study was to examine the relationship among the Self-esteem , Gratitude disposition and Happiness in Preservice Early Childhood Teachers. The subjects in this study were 192 Pre-service Early Childhood Teachers in Busan in South Korea. The findings of the study were as follows: First, the early childhood teachers considered the level of their own Happiness, Self-esteem and Gratitude disposition to be above average. Second, there was a significant positive correlation among their to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
3
0
1
Order By: Relevance
“…Another finding in this study supports the association between gratitude and happiness. Gratitude can increase a person's positive effect, which then makes them happier (Hwang et al, 2015). This is in line with other research, which has found that gratitude is more strongly associated with positive rather than negative effects Hence, a feeling of gratitude is more closely associated with happiness than a lack of it being associated with the inability to adjust (Portocarrero et al, 2020).…”
Section: │ 271supporting
confidence: 89%
“…Another finding in this study supports the association between gratitude and happiness. Gratitude can increase a person's positive effect, which then makes them happier (Hwang et al, 2015). This is in line with other research, which has found that gratitude is more strongly associated with positive rather than negative effects Hence, a feeling of gratitude is more closely associated with happiness than a lack of it being associated with the inability to adjust (Portocarrero et al, 2020).…”
Section: │ 271supporting
confidence: 89%
“…Meanwhile, the partial mediating relationship in this study proved the role of a more robust direct relationship between self-esteem and psychological well-being. In several studies, high self-esteem was generally closely associated with well-being, life satisfaction, and happiness (Dogan, Totan, & Sapmaz, 2013;Enwere & Mbakwe, 2021;Hwang, Kang, Tak, & Lee, 2015;Poudel, Gurung, & Khanal, 2020). Coopersmith (1967) defines high self-esteem as a positive evaluation of oneself in which positive emotions trigger and build psychological resilience and enhance emotional well-being (Fredrickson, 2001;.…”
Section: Sem Analysis Of the Structural Model Of Psychological Well-b...mentioning
confidence: 99%
“…La autoestima funciona como predictor de la felicidad (Hwang et al, 2015), la cual es vital para el profesorado porque de ella depende, en gran medida, el aprendizaje, las interacciones, los vínculos positivos, la autonomía, la empatía, la sensibilidad, la intuición social, el altruismo, la creatividad, las posturas críticas y, de alguna manera, el fomento del pensamiento. Además, Phillips (2021) señala la importancia y relevancia del ámbito espiritual para la autoestima.…”
Section: Autoimagen Autoconcepto Y Autoestima Del Profesoradounclassified